IMAGE PROCESSING AT ELLIPSOIDAL PHOTOMETRY - M. A. Bezuglyi; N. V. Bezuglaya; A. B. Samilyak (Приборы и методы измерений)
Ellipsoidal photometry using Charge-Coupled Device (CCD photometry), as a new kind of optical diagnostics of scattering media in reflected and/or transmitted light, requires the development of specific principles of data analysis. The object of this work was substantiation the principles of ellipsoidal CCD photometry at implementation of a new data processing method of spatial distribution of scattered optical flux. Procedure of photometric analysis include the steps of determining the image significance, as well as the size, configuration and illuminance in its respective areas with regard to the criteria to optimize the shape and sensitivity of the zone. Zone analysis schemes of photometric images for media with a radially symmetric and directed scattering are developed. Recommended to use the method of comparison with etalon for studies the technical surfaces and turbid media to determine their roughness and optical characteristics, respectively. During the analysis of biological media, there is a possible of prognosis the spatial distribution of the brightness of the image by means of statistical modeling of optical radiation in the system «biological medium + ellipsoidal reflector». That confirmed by comparing results of the numerical (direct Monte Carlo simulation) and the real experiment for samples different thickness of muscle porcine tissue in vitro. Parameters of the optical radiation, which used as input data for the simulation, correspond to a laser wavelength of 632.8 nm with a Gaussian distribution profile of power of 2 mW. As a CCD detector was used monochrome camera DMK-21Au04.AS, and ellipsoidal reflector with an eccentricity of 0.66 and working aperture of 33.75 mm. Obtained results of zone distribution of illumination across the field in real experimental photometric images during biometrics showed correlation with the total transmission, absorption and diffuse scattering coefficients. This interdependence may be important part of improvement inverse methods of determination the optical parameters of biological media.